VALIDITY , PRACTICALITY, AND EFECTIVENESS OF STUDENT WORKSHEET BASED LITERACY OF SCIENCE ON THE TOPIC PROTISTS FOR GRADE X SENIOR HIGH SCHOOL - Wulandari, Evi; Raharjo, Raharjo (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2018)
Protists topic contained many concepts that required a sample from the environment in order the students can understand the concepts easily. The student worksheet neede in learning proceses because of there was a topic, practical guides, items with examples of problems in the environment that could help students to understand the topic. Literacy of science was the ability of students to the problems of science related to the environment. Student worksheet based literacy of science was wished to help the students in guiding the practical as well as to collected data experimental results. This research was aimed to produce student worksheet based literacy of science and describe validity, practicality, and effectiveness of student worksheet based literacy of science on the topic Protists in an effort to improve learning outcomes for grade X senior high school. Student worksheet was developed using 3-D models (define, design, develope). The subjects were 20 students of grade X MIA 6 in SMAN 2 Sidoarjo. The validity of student activity sheet obtained based on the validation of two lecturers and teachers of biology SMAN 2 Sidoarjo. Practicality was obtained based on implementation to learning and student response. The effectiveness was obtained based on the results of student learning. The study of the validity indicated the percentage of student activity sheet based literacy of science were 97.63% so as to obtain very valid category. The results showed the percentage implementationÂ  practicality of learning were 97.73%, so included in the category of very practical, while the percentage of students response to student worksheet based literacy of science is 93.5% with the category of very practical use in study. The results indicated the effectiveness of learning outcomes were the percentage of 82.81% so included in the category complete. So that, it could conclude that the developed worksheet was valid, practical and effective.Keywords:Â  Student worksheet, Science Literacy, Learning Outcomes, Protists.